Nutritional Status and Factors Affecting Food Intake among Hospitalized Patients in Hospital Ampang - Mohd Nasir, Siti Anissa; Shaharuddin, Izyan Faiqah; Ismail, Nazrul Hadi; Zaman, Mazuin Kamarul; Rasimun, Siti Ramlah Rasimun (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
The study aims to measure the current nutritional status and factors contributing to food consumption during hospitalization at Hospital Ampang. This is a cross-sectional study of 206 patients consisting of 104 males and 102 females respectively between 18 to 70 years of age. Data obtained from Factors Influencing Dietary Intake of Hospitalized Patients Questionnaire and Nutritional Risk Screening (NRS 2002). We used standardized methods to measure weight, height. Body weight categories were defined based on Body Mass Index (BMI). The BMI of participants was 26.08±4.56 kgm-2 and 52.0% (107) of participants had low risk of malnutrition and at risk of malnutrition. 85.4% admitted that the food tasted different. To conclude, patients’ low consumption of food during hospitalization should be enhanced. Thus, it is essential to implement effective strategies and interventions to increase dietary intake among hospitalized patients to fulfill their nutritional requirements and encourage quick recovery.